Systemic Inflammatory Markers and Clinical Outcomes of Open versus Biportal Endoscopic Transforaminal Lumbar Interbody Fusion - Feng L; Liang J; Wang N; Zhang Q (Dove Medical Press, 2024)
Liwen Feng,1 Junbo Liang,1 Naiguo Wang,2 Qingyu Zhang2 1Department of Orthopedics, Weihaiwei People's Hospital, Weihai, Shandong Province, 264200, People's Republic of China; 2Department of Orthopedics, Shandong Provincial Hospital Affiliated to Shandong First Medical University, Jinan, Shandong Province, 250021, People's Republic of ChinaCorrespondence: Qingyu Zhang, Tel +86-13296402823, Email zqy2008512@163.com; zqy2008512@126.com; zhangqingyu@sdfmu.edu.cn Naiguo Wang, Tel +86-13505319917, Email naiguow@outlook.comPurpose: The purpose of this study is to preliminarily assess the change in perioperative systemic inflammatory markers and clinical outcomes between open TLIF and BE-TLIF procedures.Patients and Methods: In total, 38 patients who underwent single-level lumbar fusion surgery (L4-5 or L5-S1) were retrospectively reviewed. 19 patients were treated by the BE-TLIF technique, while the other patients were managed using open TLIF. The perioperative serum C-reactive protein (CRP), neutrophil/lymphocyte ratio (NLR), lymphocyte/monocyte ratio (LMR), and platelet/lymphocyte ratio (PLR) of the two groups were compared to determine if there was a statistical difference. Meanwhile, clinical evaluations were conducted to assess various factors including operative duration, estimated blood loss (EBL), drainage catheter stay, length of hospitalization, visual analogue scale (VAS), and Oswestry disability index (ODI) scores.Results: The perioperative analysis revealed that BE-TLIF cases experienced a longer operative duration than open TLIF cases (open TLIF: 138.63 ± 31.59 min, BE-TLIF: 204.58 ± 49.37 min, p < 0.001). Meanwhile, the EBL showed an increased trend in the BE-TLIF group (260.7 ± 211.9 mL) in comparison with the open TLIF group (200.9 ± 211.9 mL) (p =0.485). In terms of systemic inflammatory markers, the mean postoperative CRP, NLR, LMR, and PLR were lower in the BE-TLIF group than in the open TLIF group, although these differences were not statistically significant (p > 0.05). The VAS and ODI scores in both groups were significantly improved after surgery (p < 0.05).Conclusion: There was no significant difference found between BE-TLIF and open TLIF in terms of systemic inflammatory markers, and clinical outcomes. Overall, BE-TLIF can be considered a viable choice for lumbar canal decompression and interbody fusion for less invasion. It is worth noting that BE-TLIF does have a longer operation time, indicating that there is still potential for further improvement in this technique.Keywords: transforaminal lumbar interbody fusion, unilateral biportal endoscope, systemic inflammatory markers